The numerical modelling of the bosphorus - Ozturk, Mehmet N.; Aydogan, Burak; Yuksel, Yalcin; Cevik, Esin (INTERNATIONAL SOCIETY OFFSHORE& POLAR ENGINEERS, 2006)
Stratified flow is a flow system which has two different flows with different density in flow area. Layers are separated from each other by an interval plane. Interval plane is a physical line on which properties of flow and fluid go through each other and there can occur sudden changing and momentum transfer between layers with strong three dimensional turbulence structures. In this work, three dimensional hydrodynamic modeling of Bosphorus which shows typical behaviors of a stratified flow was done with Mike 3 software package which is capable of three dimensional free surface hydrodynamic modeling. After doing some simplifications on Bosphorus bathymetry and giving water level difference and salinity difference at the open boundaries (at the two entrances of the channel), the model was run using k-epsilon turbulence choice. Using the k-s turbulence choice, it was seen that the model gave more sophisticated results similar to Bosphorus flow pattern. The model has not been calibrated yet. Because this work's aim is to investigate whether the k-s turbulence choice gives realistic results close to the strait's physical turbulence structure.
Keywords: Engineering